Impact of Friendship Bench problem-solving therapy on adherence to ART in young people living with HIV in Zimbabwe: A qualitative study. - Ilhame Ouansafi; Dixon Chibanda; Epiphania Munetsi; Victoria Simms (PLoS ONE)
Background Adolescents and young people globally are highly vulnerable to poor mental health especially depression, and they account for 36% of new HIV infections in Eastern and Southern Africa. HIV services remain inadequate for this population and their adherence to ART is low. The Friendship Bench (FB), an evidence-based model developed in Zimbabwe to bridge the mental health gap, is a brief psychological intervention delivered on benches in primary care facilities by lay health workers ("grandmothers") trained in problem-solving therapy. This study explored the experience of young people living with HIV attending FB, and their perception of how problem-solving therapy impacted their adherence to ART. Methods Semi-structured interviews were conducted in July 2019 with 10 young people living with HIV aged 18-24 years, who had recently completed FB counselling in Harare. Participants were purposively sampled and recruited from three primary care facilities. Interviews were conducted in Shona, audio-recorded, transcribed verbatim and translated into English. Transcripts were analysed in NVivo12 using inductive thematic analysis. Results Study findings revealed a clear emotional denial towards HIV, particularly for young people infected perinatally, and a resulting low adherence to ART. The study also unpacked the issues of internal stigma and how young people living with perinatally acquired HIV are informed of their HIV status. Participants reported that FB had a critical role in helping them accept their HIV status. Grandmothers' empathic attitude was key during counselling on adherence to ART, to demystify the disease and treatment, normalize the reality of living with HIV, encourage young people to socialize with peers and free them of guilt. Interviewees unanimously reported improved ART adherence following FB counselling, and many described enhanced health and wellbeing. Conclusion Participants saw FB as a strong contributor to their general well-being, evident in decreased symptoms of depression and improved adherence to ART. FB problem-solving therapy should be rolled out to further support young people after post-test counselling or HIV serostatus disclosure for perinatally acquired HIV, for acceptance of HIV status and adherence to ART.